2014
DOI: 10.1007/s12576-014-0335-6
|View full text |Cite
|
Sign up to set email alerts
|

High dose of aspirin moderates diabetes-induced changes of heart glycogen/glucose metabolism in rats

Abstract: Aspirin (ASA), as a multifunctional drug has been used as a hypoglycaemic agent in the treatment of diabetes and severe hyperglycaemia and has been established as a secondary strategy which may prevent many cardiovascular events. In this study we investigated high dose (100 mg/kg b.w./i.p) and time-dependent (2, 7 and 14 days) effects of ASA on the heart key enzymes and substrates from glycogen/glucose metabolism in control and diabetic rats. The results accomplished demonstrated that ASA significantly potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
(64 reference statements)
1
7
0
Order By: Relevance
“…In our results, the accumulation of kaempferol and rutin increased signi cantly after UV-B treatment, especially under moderate radiation, suggesting that they are the main ultraviolet absorbing substances. Salicylic acid (C6C1-type), a compound that reduces the risk of long-term heart disease in diabetic patients, increases signi cantly in A. senticosus plants when exposed to moderate UV-B radiation (Farthing et al 2007;Nulton-Persson et al 2004;Eisen et al 2009;Dervisevik et al 2014). Therefore, it can be inferred that an appropriate amount of UV-B radiation application to the plant may improve the medicinal effect of A. senticosus extract, with relation to heart disease and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In our results, the accumulation of kaempferol and rutin increased signi cantly after UV-B treatment, especially under moderate radiation, suggesting that they are the main ultraviolet absorbing substances. Salicylic acid (C6C1-type), a compound that reduces the risk of long-term heart disease in diabetic patients, increases signi cantly in A. senticosus plants when exposed to moderate UV-B radiation (Farthing et al 2007;Nulton-Persson et al 2004;Eisen et al 2009;Dervisevik et al 2014). Therefore, it can be inferred that an appropriate amount of UV-B radiation application to the plant may improve the medicinal effect of A. senticosus extract, with relation to heart disease and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that aspirin alone has no positive effect on lipid profile improvement. However, some recent studies reported that high-dose aspirin influences lipid metabolism [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin is a commonly used medication to prevent cardiovascular disease, which has been identified as an inhibitor of glycolysis. Dervisevik et al [3] reported that aspirin impaired glycolysis in diabetic rat heart as a result of decreased phosphofructokinase (PFK) activity. In addition, aspirin was suggested to attenuate glycolysis in HCT-116 colon cancer cells by acetylation of glycolytic pathway enzymes [4].…”
Section: Dear Editormentioning
confidence: 99%